United States : Publication of Financial Sector Assessment Program Documentation; Technical Note on Regulatory Reform; OTC Derivatives. (IMF Staff Country Reports; Country Report ;, 2010)
OTC derivatives markets were an increasing source of vulnerability heading into the crisis. OTC derivatives markets contributed to the financial crisis. Credit derivatives facilitated the development and growth of the structured securities markets; and the purchasing, packaging, and distribution of poorly underwritten loans and mortgages. The proposed reforms will make major improvements to market trading liquidity and the price discovery process. The reversal of the deregulation of OTC derivatives marks a major improvement in regulatory approach, and it closes an important gap in the regulatory framework.